Energy assesment in a single household to increase awareness of energy usage / Nur Alia Shahirah Ruzali - Ruzali, Nur Alia Shahirah (2022)
In this study, student from Mechanical Engineering Course has performed an analysis on energy assessment in a single household to increase awareness of energy usage in residential area that have 3 rooms. As we know, energy is one of the most important sources in our daily lives. If energy sources are used excessively, it can cause increased risk of climate change and can increased carbon footprint. For this assessment, there are several objectives that need to be achieved, which are to determine electrical appliances that make use of energy and to assess the energy consumption for a house, contain 3 rooms. It is expected having an awareness will help in adapting energy usage in their daily life. The methodology used in this study is by doing Preliminary Energy Audit which require to collect data energy usage in 3 different houses with multiple number of household members. After data has been collected, the researcher will calculate the energy usage by using the standard tariff used in Malaysia. For the result, the researcher can analyze the cost for energy consumption in all 3 houses. In house 1, since the number of household members is the highest among the others, the energy consumption in that house is high. This is because there are lot of electrical appliances that has been installed in the house. For house 2, the number of household member is only 1 person and this make this house has lowest energy cost per month while the last house has 3 persons living there. From the result, the main factor that can increase the energy usage in a house is the number of household member. The greater the amount of household members, the more energy usage in a house. Besides that, the factor can also change the cost for energy usage is type of home and their characteristic, the geographic location and climate.